2015
DOI: 10.1371/journal.pone.0126863
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Antibodies in Lymphocyte Supernatant in Diagnosing Tuberculosis in Severely Malnourished Children Presenting with Pneumonia

Abstract: BackgroundThe diagnosis of tuberculosis (TB) in young children can be challenging, especially in severely malnourished children. There is a critical need for improved diagnostics for children. Thus, we sought to evaluate the performance of a technique that measures antibodies in lymphocyte supernatant (ALS) for the diagnosis of TB in severely malnourished children presenting with suspected pneumonia.MethodsChildren less than 5 years with severe acute malnutrition and radiological features of pneumonia admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…Within the members of the control population, 22% demonstrated a positive MASC result yielding a specificity value of 78%. While this is lower than the 87% specificity initially reported in children from Bangladesh, it is much higher than the 51% specificity subsequently found among children Ͻ5 years of age admitted with radiographic pneumonia and severe acute malnutrition (8,9). We deemed these to be false-positive results for active TB because the control children in our study had no reported risk factors, symptoms, or clinical findings consistent with TB.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Within the members of the control population, 22% demonstrated a positive MASC result yielding a specificity value of 78%. While this is lower than the 87% specificity initially reported in children from Bangladesh, it is much higher than the 51% specificity subsequently found among children Ͻ5 years of age admitted with radiographic pneumonia and severe acute malnutrition (8,9). We deemed these to be false-positive results for active TB because the control children in our study had no reported risk factors, symptoms, or clinical findings consistent with TB.…”
Section: Discussioncontrasting
confidence: 63%
“…Initial reports of this assay in childhood TB suggested a correlation with bacillary burden; serial measurements demonstrated reductions in ALS titers which correlated well with clinical treatment response among culture-confirmed TB cases (8,12). However, subsequent reports from studies performed with young malnourished children suggested that this assay did not outperform clinical scoring systems for diagnosis of disease in children with TB such as the Kenneth-Jones and WHO scoring criteria (9).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In recent studies, however, ALS assays have been successfully carried out in the pediatric population in the field using a small volume of blood samples (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The lesser performance of ALS in relation to MKJC scoring and the WHO criteria for the diagnosis of TB in our study population is interesting but critically important for the clinician in resource poor settings. The published data from the same cohort already revealed that ALS was not sufficiently accurate to improve the diagnosis of TB in severely malnourished children (15). However, that article did not reveal the comparative performance of ALS with MKJC scoring and the WHO criteria for the diagnosis of TB in our study population.…”
Section: Discussionmentioning
confidence: 99%